Unidade demonstrativa de restauração ecológica introduzida em agroecossistema degradado, no Alto Rio São Lourenço, Campo Verde-MT - Souza, William Pietro de (2012)
Mato Grosso has one third of its area or degraded in the process of progressive degradation, which represents around 33 million hectares. The aim of the study was to evaluate the potential of seed rain and “seed muvuca” (nucleation techniques) to support the establishment of demonstration units for ecological restoration (UDRE), in an environment where extensive grazing predominates at high São Lourenço, in Campo Verde, southeastern Mato Grosso. To evaluate the production of seed rain in three forest fragments, located in the rural area, the installation took place fifteen collectors made with PVC pipes and nylon fabric (mesh 1 mm × 1 mm) with 1 m², suspended to 80cm from the ground. The material was collected monthly and the seeds were separated and quantified as the dispersion syndrome, lifestyle and stage succession. It was determined the density and absolute frequency diversity index and evenness. Already on a stretch of Permanent Preservation Areas degraded tested the manual planting "seeds muvuca" as environmental remediation technique. This planting was organized into four treatments, which differed in terms of seed size and presence / absence of pigeon pea (Cajanus cajan) as a buffer zone. The field data were georeferenced and compose a database hosted on geographic geographic information system (GIS). Regarding the seed rain were obtained 3622 seeds, belonging to 74 taxa. Most of the seeds collected are dispersed by wind (74%). Aiming the process of forest recovery, are cited as important taxa for reforestation in the region of Capim Branco (Campo Verde-MT): Tachigali rubiginosa, Siparuna guianensis, Nectandra sp., Cordia alliodora, Alibertia sp., Terminalia brasiliensis and Myrcia sp. representatives of groups of trees that showed the highest yields and the abundance of seeds in the seed rain. Regarding the muvuca planting of seeds, the species that showed better growth rate were Enterolobium contortisiliquum, Dipteryx alata, Sterculia chicha and Copaifera langsdorfii. These species have the potential to be used in the method of regeneration by direct seeding. The use of pigeon pea was not efficient for values increases germination, survival and percentage of individuals established. The technique of planting “seed muvuca” manual was feasible to be adopted in the recovery of degraded areas of permanent preservation, especially for small territorial extensions.